2020
DOI: 10.1007/s13300-020-00804-2
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy and Safety of Dulaglutide by Baseline HbA1c in Chinese Patients with Type 2 Diabetes: A Post Hoc Analysis

Abstract: Introduction: To evaluate the efficacy and safety of dulaglutide 0.75 and 1.5 mg in patients with type 2 diabetes mellitus (T2DM) by baseline glycated hemoglobin (HbA1c) \ 8.5% or C 8.5% after 26 weeks of treatment.Methods: Assessment of the Weekly Admin-istRation of dulaglutide in Diabetes (AWARD) China 1 (CHN1) study (NCT01644500, n = 556) included patients on dulaglutide vs. glimepiride who were treatment naïve or on monotherapy but discontinued therapy. AWARD-CHN2 (NCT01 648582, n = 591) patients were on d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
5
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 22 publications
2
5
0
Order By: Relevance
“…However, HbA1c was significantly reduced in individuals with T1D or T2D with a baseline HbA1c level > 8.5%; this was not observed for those who already had better glycaemic control before switching to faster aspart (baseline HbA1c ≤ 8.5%). This is in agreement with previous studies, which found that patients with a baseline HbA1c of ≤ 8.5% had a lesser reduction in HbA1c in response to insulin treatment, compared with those with baseline HbA1c > 8.5% [ 20 , 21 ]. Additional analyses showed that an improvement in HbA1c can be achieved with faster aspart, regardless of prior exposure to SGLT2i or GLP-1 RA.…”
Section: Discussionsupporting
confidence: 93%
“…However, HbA1c was significantly reduced in individuals with T1D or T2D with a baseline HbA1c level > 8.5%; this was not observed for those who already had better glycaemic control before switching to faster aspart (baseline HbA1c ≤ 8.5%). This is in agreement with previous studies, which found that patients with a baseline HbA1c of ≤ 8.5% had a lesser reduction in HbA1c in response to insulin treatment, compared with those with baseline HbA1c > 8.5% [ 20 , 21 ]. Additional analyses showed that an improvement in HbA1c can be achieved with faster aspart, regardless of prior exposure to SGLT2i or GLP-1 RA.…”
Section: Discussionsupporting
confidence: 93%
“…In a post-hoc analysis of two Chinese patient populations with T2DM, the efficacy of dulaglutide was further evaluated according to baseline HbA1c < 8.5% or ≥ 8.5% after 26 weeks of treatment [ 26 ]. Dulaglutide achieved a greater HbA1c reduction, combined with weight loss and lower risk of hypoglycemia, compared with active comparators (glimepiride and insulin glargine) regardless of baseline HbA1c; patients with a higher baseline HbA1c did achieve greater HbA1c reductions [ 26 ].…”
Section: Discussionmentioning
confidence: 99%
“…In a post-hoc analysis of two Chinese patient populations with T2DM, the efficacy of dulaglutide was further evaluated according to baseline HbA1c < 8.5% or ≥ 8.5% after 26 weeks of treatment [ 26 ]. Dulaglutide achieved a greater HbA1c reduction, combined with weight loss and lower risk of hypoglycemia, compared with active comparators (glimepiride and insulin glargine) regardless of baseline HbA1c; patients with a higher baseline HbA1c did achieve greater HbA1c reductions [ 26 ]. In the same Chinese populations, another post-hoc analysis showed that dulaglutide improved glycemic control combined with a slight body weight reduction and low hypoglycemia risk in patients with a BMI < 25 kg/m 2 ; this result suggests that BMI is not a necessary consideration for dulaglutide treatment in Chinese patients with T2DM [ 27 ].…”
Section: Discussionmentioning
confidence: 99%
“…The effect of basal insulin was applied from the second year using data of insulin glargine. The effect of insulin glargine on HbA 1c , BMI, and hypoglycemic events among Chinese patients with T2D were derived from the study of Yu et al [37].…”
Section: Treatment Switching and Long-term Parameter Progressionmentioning
confidence: 99%